2012
DOI: 10.5005/jp-journals-10021-1064
|View full text |Cite
|
Sign up to set email alerts
|

Stress Appraisal with Simulation of en masse Absolute Intrusion of Maxillary Anteriors deploying Strategic Mini-implant Locations: A Finite Element Analysis

Abstract: One of the major challenges of fixed clinical orthodontics is the correction of deep overbite. Mini screw implants are ideally suited for absolute intrusion because they make it possible to apply light continuous forces of known magnitudes without producing any reciprocal reactionary effect on posterior teeth. The purpose of this FEM study was to evaluate and compare the stresses generated in maxillary anterior region during absolute en masse intrusion of six maxillary teeth using mini-implants at strategic lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Maximum stress was found along cervical region of labial side of central incisor followed by laterals similar to study by Sagar S Padmawar et al 8,10 probably because the point of force application is between central incisors and away from the lateral incisors.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Maximum stress was found along cervical region of labial side of central incisor followed by laterals similar to study by Sagar S Padmawar et al 8,10 probably because the point of force application is between central incisors and away from the lateral incisors.…”
Section: Discussionsupporting
confidence: 82%
“…Studies have also shown that range of stresses exerted by the blood in capillary vessels (0.0026N/mm 2 ) help us to determine the changes in tooth structure at apex leading to root resorption. 8,10 Few literature consider 0.0047 MPa as the range of capillary blood pressure 26 .All the values of Von Mises stress on tooth in above method are found to be above the capillary blood hydrostatic pressure suggesting the possibility of root resorption.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…At the center of resistance and 2 mm above and below it, teeth moved bodily by 0.013 mm Padmawar et al . [ 18 ] evaluated and compared the stresses generated in the maxillary anterior region during absolute en masse intrusion of six maxillary teeth using mini-implants at two different points of force applications. The study found that use of bilateral implants was more efficient and less detrimental for the teeth during absolute intrusion of the maxillary anterior teeth Chetan et al .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies evaluated the stress in the bone [10, 11], PDL [12–18], implants [19–22] in mini-implant-assisted retraction [23] with different height of implants and retraction hooks [24, 25] and materials [26, 27]. But there are no studies which evaluated the stresses on the bone and PDL in two implant and three implant combinations.…”
Section: Introductionmentioning
confidence: 99%